2011
DOI: 10.1186/1471-2458-11-529
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported health status and access to health services in a sample of prisoners in Italy

Abstract: BackgroundSelf-reported health status in underserved population of prisoners has not been extensively explored. The purposes of this cross-sectional study were to assess self-reported health, quality of life, and access to health services in a sample of male prisoners of Italy.MethodsA total of 908 prisoners received a self-administered anonymous questionnaire pertaining on demographic and detention characteristics, self-reported health status and quality of life, access to health services, lifestyles, and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
41
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 26 publications
16
41
0
9
Order By: Relevance
“…Results confirmed former studies in that prisoners have their own opinion about poor health, high morbidity rate, and the frequency of visiting prison health services (Nobile, Flott, Nicotera, Pileggi & Angelillo, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…Results confirmed former studies in that prisoners have their own opinion about poor health, high morbidity rate, and the frequency of visiting prison health services (Nobile, Flott, Nicotera, Pileggi & Angelillo, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…Prisoners' poor health status as well as a high prevalence of mental disorders and mental health deprivation have been reported in various studies [3,5,8,[55][56][57][58][59]. Furthermore, it is confirmed that prisoners report a deterioration of their health status during their detention [3,30,[60][61][62].…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, it is confirmed that prisoners report a deterioration of their health status during their detention [3,30,[60][61][62]. The age constitutes an important factor.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations